Locating a National Collection project website - Gadd, Stephen; Simon, Rainer; Rees, Gethin; Isaksen, Leif (British Library, 2022)
Project website for the Locating a National Collection (LaNC) project that houses instances of LaNC’s Peripleo maps interface alongside descriptive text (https://github.com/britishlibrary/locating-a-national-collection). The website was built using Joe Padfield’s simple-site, many thanks to him (https://github.com/jpadfield/simple-site). LaNC was a Foundation project within the AHRC-funded Towards a National Collection Programme.